Selective Carboxylesterase Inhibitors for Improving Efficacy, Safety and Rational use of Ester-Containing Drugs - Boltneva, N.P.; Makhaeva, G.F.; Shchegol’kov, E.V.; Burgart, Ya.V.; Saloutin, V.I. (Biomedical Chemistry: Research and Methods, 2018)
In clinical practice, a large number of prodrugs and active drugs containing an ester, carbamate or amide moiety are used. Carboxylesterase (CaE, EC 3.1.1.1) is the key enzyme of hydrolytic metabolism of such drugs in the body, it largely determines their pharmacokinetics, bioavailability, efficacy and possible toxic effects. Using CaE selective inhibitors as components of combined drug therapy it is possible us to regulate the rate of hydrolytic transformation of ester-containing drugs and opens the possibility of their rational use. The development of effective and selective CaE inhibitors suitable for in vivo application is a new promising approach in medicinal chemistry and pharmacology that allows to improve the efficacy, bioavailability and reduce the side effects of ester-containing drugs.